The effects of non-nutritive sweeteners in Florence’s Homestyle Cha-Cha - Boone, Leslie (Kansas State University, 2011)
Non-nutritive sweeteners are alternative sweeteners that provide the taste of sweetness without a caloric contribution. In this Florence’s HomeStyle Cha-Cha study, aspartame, acesulfame K, sodium saccharin, and neotame were evaluated as a substitute for sucrose in the formulation. These sweeteners were used at their recommended equivalency levels to match the sweetness potency level to that of sucrose. Because they are more potent than sucrose, minimum amounts were needed to replace sucrose, and the remaining amounts were filled with maltodextrin. Using maltodextrin as bulk filler is common practice in the industry when replacing sucrose with a non-nutritive sweetener. This study evaluated the quality of the finished product in determining which non-nutritive sweetener had similar taste, aroma, and density qualities as the control, which was Cha-Cha sweetened with sucrose. The results of the evaluations indicated that Cha-Cha sweetened with acesulfame K was more similar to the control than the other non-nutritive sweeteners. Of the three taste characteristics evaluated for their degree of intensity, sweetness, saltiness, and bitterness, the acesulfame K sweetened treatment was closer to the control. In the GC/MS analysis in characterizing the volatile aroma compounds, acesulfame K contained all the aroma compounds with smaller differences in concentration than the other experimental treatments. In the density evaluation, the experimental treatments were similar to the control treatment. In conclusion, Florence’s HomeStyle Cha-Cha sweetened with acesulfame K is similar in quality to the sucrose-sweetened control.
Keywords: Processing; Non-nutritive sweetners; Food Science (0359)